Retrospective overview of the coronavirus disease 2019 (COVID-19) outbreak in Mauritania (2020)
A COVID-19 outbreak is currently ongoing in Mauritania. Until July 1, 2020, Mauritania health authorities reported 41,862 serological and RT-qPCR tests performed, of which 4,472 (10.7%) were positive for SARS-Cov-2. Males were significantly more affected (57.1%) than females (42.9%). Individuals of the age groups 15–34 (35.8%) and 35–54 (36.6%) years were the most affected. There were 129 (2.9%) deaths, 1,677 (37.5%) recoveries and 2,666 (59.6%) active cases of whom 2,261 (84.8%) were asymptomatic, 394 (14.7%) with mild symptoms and 11 (0.4%) severe cases. A large proportion of fatalities (72%; 85/118) occurred among adults aged ≥ 55 years. Of 4,472 positive cases, 4,241 (94.8%) were infected through contact with a confirmed COVID-19 case, 133 (3.0%) had no contact with confirmed COVID-19 case, and 98 (2.2%) were imported. As a riposte against COVID-19, the Mauritanian authorities announced a set of preventive measures, including closure of land and air borders, nocturne curfew, closure of markets, schools, and universities, and restriction of movement between cities. Control measures include the systematic testing of symptomatic patients, isolation and management of active cases, contact tracing, and quarantine of people who have been in contact with a COVID-19-positive individual. We discuss the efforts of the Mauritanian government to combat this potentially life-threatening pneumonia.